In Silico Analysis of Pongamia pinnata to Inhibit Neuronal Apoptosis after Ischemic Stroke via NMDAR and Caspase-3 - Muhammad Ja'far Shodiq; Farmindo Hartono; Siti Khaerunnisa; Abdulloh Machin (AKSONA, 2023)
Highlight: The potential of Pongamia pinnata as an inhibitor of apoptosis in ischemic stroke has never been evaluated before. Pongamia pinnata has potential to inhibit neuronal apoptosis via NMDAR and Caspase-3 in ischemic stroke. Karanjachromene has the best binding interaction to inhibit NMDAR.   ABSTRACT Introduction: One of the cardiovascular diseases with the highest mortality rate is stroke. Stroke is the second-leading cause of death worldwide. Each year, 12.2 million new cases of stroke occur, of which 7.6 million are ischemic strokes. In ischemic stroke, there are several pathways that cause neuronal apoptosis. The activity of NMDAR and caspase-3 is one of the pathways. Pongamia pinnata phytochemicals have a neuroprotective function against neurological disorders. However, its use as an inhibitor of apoptosis in ischemic stroke has never been evaluated before. Objective: This research was designed to evaluate the phytochemicals of Pongamia pinnata as inhibitors of neuronal apoptosis in ischemic stroke using an in silico study. Methods: This study used four main phytochemicals of Pongamia pinnata, namely Karanjin, Karanjachromene, Pongapin, and Pongachromene. The protein targets for neuronal apoptosis were NMDAR and caspase-3. The molecular docking processes were ligand preparation, protein preparation, grid box determination, molecular docking, and visualized molecular docking. Results: In silico results showed that at NMDAR target proteins, Karanjin, Karanjachromene, Pongapin, and Pongachromene have binding energies of -5.12, -5.83, -5.03, and -5.13 kcal/mol. At protein targets, Caspase-3, Karanjin, Karanjachromene, Pongapin, and Pongachromene have binding energies of -4.87, -4.98, -4.88, and -5.08 kcal/mol. Conclusion: The phytochemicals of Pongamia pinnata have the potential to inhibit neuronal apoptosis via NMDAR and caspase-3 in ischemic stroke. The binding of Karanjachromene to NMDAR demonstrated the compound's best interaction.